Gα and regulator of G‐protein signaling (RGS) protein pairs maintain functional compatibility and conserved interaction interfaces throughout evolution despite frequent loss of RGS proteins in plants. Issue 2 (16th September 2016) - Hackenberg, Dieter; McKain, Michael R.; Lee, Soon Goo; Roy Choudhury, Swarup; McCann, Tyler; Schreier, Spencer; Harkess, Alex; Pires, J. Chris; Wong, Gane Ka‐Shu; Jez, Joseph M.; Kellogg, Elizabeth A.; Pandey, Sona
Summary: Signaling pathways regulated by heterotrimeric G‐proteins exist in all eukaryotes. The regulator of G‐protein signaling (RGS) proteins are key interactors and critical modulators of the Gα protein of the heterotrimer. However, while G‐proteins are widespread in plants, RGS proteins have been reported to be missing from the entire monocot lineage, with two exceptions. A single amino acid substitution‐based adaptive coevolution of the Gα:RGS proteins was proposed to enable the loss of RGS in monocots. We used a combination of evolutionary and biochemical analyses and homology modeling of the Gα and RGS proteins to address their expansion and its potential effects on the G‐protein cycle in plants. Our results show that RGS proteins are widely distributed in the monocot lineage, despite their frequent loss. There is no support for the adaptive coevolution of the Gα:RGS protein pair based on single amino acid substitutions. RGS proteins interact with, and affect the activity of, Gα proteins from species with or without endogenous RGS. This cross‐functional compatibility expands between the metazoan and plant kingdoms, illustrating striking conservation of their interaction interface. We propose that additional proteins or alternative mechanisms may exist which compensate for the loss of RGS in certain plant species.